2016
DOI: 10.1002/pola.28374
|View full text |Cite
|
Sign up to set email alerts
|

Tunable, concentration‐independent, sharp, hysteresis‐free UCST phase transition from poly(N‐acryloyl glycinamide‐acrylonitrile) system

Abstract: Poly(N‐acryloylglycinamide‐co‐acrylonitrile) (poly(NAGA‐AN)) copolymers were synthesized using reversible‐addition‐fragmentation transfer polymerization. In contrast to poly(NAGA) the thermoresponsive behavior of poly(NAGA‐AN) shows a narrow cooling/heating hysteresis in water with a tunable cloud point, depending on the acrylonitrile amount in polymer. Furthermore, we showed that there is no significant effect of the solution concentration on the cloud point and stable phase transition behavior in electrolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 33 publications
(66 reference statements)
1
37
0
Order By: Relevance
“…The latter contain H‐donor and H‐acceptor sites, which are able to form intra‐molecular reversible hydrogen bonds (globule conformation below UCST) and inter‐molecular bonds with water (coil conformation above UCST). [ 11–21 ] The non‐ionic polymers have attracted a great deal of attention due to their insensitivity to salts, which make them more attractive for applications in physiological environment. [ 22–24 ] During the last decade, efforts have been focused toward developing novel water‐soluble copolymers exhibiting UCST behavior by copolymerizing H‐donor monomers ( N ‐acryloyl glycinamide [ 11–16 ] or acrylamide [ 15,17–21,25 ] ) and H‐acceptor monomers (acrylonitrile, [ 11,15,18,19,21,25,26 ] styrene, [ 15,17 ] and butyl acrylate [ 15 ] ).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The latter contain H‐donor and H‐acceptor sites, which are able to form intra‐molecular reversible hydrogen bonds (globule conformation below UCST) and inter‐molecular bonds with water (coil conformation above UCST). [ 11–21 ] The non‐ionic polymers have attracted a great deal of attention due to their insensitivity to salts, which make them more attractive for applications in physiological environment. [ 22–24 ] During the last decade, efforts have been focused toward developing novel water‐soluble copolymers exhibiting UCST behavior by copolymerizing H‐donor monomers ( N ‐acryloyl glycinamide [ 11–16 ] or acrylamide [ 15,17–21,25 ] ) and H‐acceptor monomers (acrylonitrile, [ 11,15,18,19,21,25,26 ] styrene, [ 15,17 ] and butyl acrylate [ 15 ] ).…”
Section: Figurementioning
confidence: 99%
“…[ 11–21 ] The non‐ionic polymers have attracted a great deal of attention due to their insensitivity to salts, which make them more attractive for applications in physiological environment. [ 22–24 ] During the last decade, efforts have been focused toward developing novel water‐soluble copolymers exhibiting UCST behavior by copolymerizing H‐donor monomers ( N ‐acryloyl glycinamide [ 11–16 ] or acrylamide [ 15,17–21,25 ] ) and H‐acceptor monomers (acrylonitrile, [ 11,15,18,19,21,25,26 ] styrene, [ 15,17 ] and butyl acrylate [ 15 ] ). Such (co)polymers have been mainly prepared using free radical polymerization [ 11,14–17,26 ] and by thermally initiated controlled radical polymerization such as atom transfer radical polymerization [ 13 ] and reversible addition fragmentation chain transfer (RAFT) [ 11,12,16–19,25 ] The impacts of various parameters on the UCST phase transition, including salts, pH, molecular weight, molecular weight distribution, and chemical composition, have been well evaluated.…”
Section: Figurementioning
confidence: 99%
“…Hydrolysis of the amide group of PNAGA and use of ionic initiators in radical polymerization are other factors, which contribute in suppressing the UCST behavior of polymer [42]. However, it has been observed that polymer concentration in solution affects the UCST, and therefore Käfer et al [44] synthesized a copolymer of PNAGA using AN as second block (Figure 9) to avoid the effect of concentration and to retain narrow cooling/ heating hysteresis in water. The T pt of copolymer P(NAGA-co-AN) was found to be independent of polymer concentration, and can be easily tuned by altering the AN content in copolymer.…”
Section: Poly(n-acryloylglycinamide)mentioning
confidence: 99%
“…Copolymerization of N-acryloyl glycinamide and acrylonitrile by using cyanomethyl dodecyl trithiocarbonate (CMDT) as chain transfer agent and 2,2´-Azoisobutyronitrile (AIBN) as initiator[44].…”
mentioning
confidence: 99%
“…The biomedical applications of UCST polymers are strongly impeded due to the sensitivity to ionic strengths and polymer concentrations as most of the UCST polymers were based on polyzwitterions . Recently, we synthesized a series of noncharged UCST‐type polymers with tunable cloud points based on copolymers of N ‐acryloylglycinamide and acrylonitrile, which were independent on ionic strengths and polymer concentrations . Block and graft copolymers of noncharged UCST‐type segments with hydrophilic poly(ethylene glycol), poly(dimethylacrylamide), and poly( N , N ‐dimethylaminoethyl methacrylate) provide temperature dependent micellar structures which opens up an interesting future direction of thermoresponsive polymers in biomedical applications .…”
Section: Introductionmentioning
confidence: 99%